HUBUNGAN PELAKSANAAN SATU RUMAH SATU JUMANTIK TERHADAP ANGKA KEJADIAN DEMAM BERDARAH DENGUE DI DUSUN PESALAKAN DESA PEJENG KANGIN - I Putu Artha Wijaya; Alfiery Leda Kio; Dewa Gede Dharma Suasta (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Dengue Hemorrhagic Fever is a contagious disease caused by the dengue virus. The clinical manifestations of dengue hemorrhagic fever include bleeding that causes shock that leads to death. One of the controls for dengue hemorrhagic fever that can be carried out by all ages and from all levels of education is the activity of eradicating mosquito nests (PSN). Satu Rumah Satu Jumantik is a community participation in controlling vector-borne diseases, especially dengue fever through the 3M Plus PSN. This study aims to determine "the relationship between implementation of one house and one jumantik against the incidence rate of dengue hemorrhagic fever in Pesalakan, Pejeng Kangin village".This type of research is analytic observational research with a cross sectional approach. The population in this study were 92 houses with family members who carried out the Satu Rumah Satu Jumantik in Pesalakan, Pejeng Kangin Village in 2020. The sampling technique was carried out by using the total sampling technique. The instrument used in this study was a questionnaire.The results showed that there was a relationship between the implementation of Satu Rumah Satu Jumantik through the Eradication of Mosquito Nests in each house every week and the incidence of dengue hemorrhagic fever cases. The results of statistical tests with Chi Square get p value = 0.029 (<α = 0.05) there is a significant relationship between the implementation of satu rumah satu jumantik against cases of dengue hemorrhagic fever. Thus it is suggested that the community can implement the satu rumah satu jumantik in preventing cases of Dengue Hemorrhagic Fever.